Rising incidence of head and neck mucosal melanoma in Australia. (5th December 2016) - Youssef, D; Vasani, S; Marquess, J; Cervin, A
Abstract: Objective: To establish Australian population-based incidence trends for mucosal melanoma of the head and neck. Methods: Cases between 1985 and 2009 were identified in the Australian Cancer Database. Age-standardised incidence trends were established, including subgroup stratification by sex and site. Results: A continuously progressive increase in incidence was evident in the 353 cases identified over the 25-year study period. This was particularly evident in sinonasal mucosal melanoma in men, despite the overall incidence remaining higher in women. Conclusion: There is such paucity in published global incidence trends of head and neck mucosal melanoma. Comparisons of incidence patterns between countries can provide insight into aetiological factors of this rare disease.